2004
DOI: 10.1098/rspb.2003.2526
|View full text |Cite
|
Sign up to set email alerts
|

Sex–specific effects of carotenoid intake on the immunological response to allografts in guppies (Poecilia reticulata)

Abstract: Rarely are the evolutionary origins of mate preferences known, but, recently, the preference of female guppies (Poecilia reticulata) for males with carotenoid-based sexual coloration has been linked to a sensory bias that may have originally evolved for detecting carotenoid-rich fruits. If carotenoids enhance the immune systems of these fishes, as has been suggested for other species, this could explain the origin of the attraction to orange fruits as well as the maintenance of the female preference for orange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
98
4
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 40 publications
1
98
4
1
Order By: Relevance
“…Many studies have confirmed the immunostimulant properties of carotenoids (Chew 1993;Van Poppel et al 1993;McGraw & Ardia 2003;Grether et al 2004). However, few works have addressed directly whether carotenoid availability enhances parasitic resistance.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Many studies have confirmed the immunostimulant properties of carotenoids (Chew 1993;Van Poppel et al 1993;McGraw & Ardia 2003;Grether et al 2004). However, few works have addressed directly whether carotenoid availability enhances parasitic resistance.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, previous experimental studies using parasites have found that (i) controlled infections reduce the expression of carotenoid-based ornamentation (Hill & Brawner 1998;Brawner et al 2000;Horak et al 2004), (ii) parasite eradication positively affects carotenoidbased ornamentation (Martinez-Padilla et al 2007), and (iii) expression level of ornaments may indicate males' ability to clear parasite infection (Lindströ m & Lundström 2000). Furthermore, newly developed methods, which allow measurement of the magnitude of the immune response to various antigens (see Adamo (2004) for a review), made it possible to identify a positive relationship between carotenoid-based coloration and various immune effectors (Blount et al 2003;McGraw & Ardia 2003 and references therein), and have also shown that immune defence and sexual attractiveness are constrained by carotenoid availability (Blount et al 2003;Grether et al 2004;McGraw & Ardia 2004). However, the potential link between parasitic infection and expression of secondary sexual traits needs further investigation because both parasites themselves and parasitic resistance may affect ornamentation in different ways.…”
Section: Introductionmentioning
confidence: 99%
“…Animals are unable to synthesize these pigments (Goodwin 1984), and in some species, including guppies, a trade-off exists between the use of ingested carotenoids in colouration and in the immune system (Olson & Owens 1998;Blount et al 2003;Faivre et al 2003;McGraw & Ardia 2003;Grether et al 2004). The primary source of carotenoids for guppies in nature is unicellular algae, the availability of which is largely a function of the openness of the forest canopy (i.e.…”
mentioning
confidence: 99%
“…Es considerada una especie de importancia ornamental por la acuarofilia mundial (Balon 2004). Se han realizado en P. reticulata diversos estudios en el ámbito del aprendizaje y del comportamiento reproductivo (Brosnan et al 2003, Croft et al 2003, Grether et al 2003, así como modificaciones en el comportamiento por acción de pesticidas organofosforados (Selvi et al 2004). Paracheirodon innesi (Myers, 1936) "Neon Tetra" (Characidae), es una especie amazónica, domesticada y conocida por los acuaristas a nivel mundial (Balon 2004).…”
Section: Introduccionunclassified